2020
DOI: 10.1021/acs.jced.9b00922
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressure of Nine Perfluoroalkyl Substances (PFASs) Determined Using the Knudsen Effusion Method

Abstract: Sublimation vapor pressures of nine pure perfluoroalkyl substances, including ammonium perfluoro­(2-methyl-3-oxahexanoate) (GenX), 1H,1H,2H,2H-perfluoro-1-decanol (8:2 FTOH), 1H,1H,2H,2H-perfluoro-1-dodecanol (10:2 FTOH), and C6 to C11 perfluorocarboxylic acids (PFCAs), were measured using the Knudsen technique at near-ambient temperatures. Melting temperatures and fusion enthalpies of these compounds were also measured by differential scanning calorimetry. The vapor pressure of GenX ammonium salt is comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The close agreement in PFAS phase transition parameters (e.g., MP) in different atmospheres, as shown in Figure , provides a high level of confidence in the results. The DSC-derived MPs of PFOA (48–52 °C) and K-PFOS (283 °C) agree well with the literature values (46–52 °C for PFOA ,, and 277–280 °C for K-PFOS).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The close agreement in PFAS phase transition parameters (e.g., MP) in different atmospheres, as shown in Figure , provides a high level of confidence in the results. The DSC-derived MPs of PFOA (48–52 °C) and K-PFOS (283 °C) agree well with the literature values (46–52 °C for PFOA ,, and 277–280 °C for K-PFOS).…”
Section: Results and Discussionmentioning
confidence: 99%
“…These modeled trends are further supported by the experimentally derived data shown in Figure 1b and an additional study which reported boiling points of C4−C8 PFCAs and PFSAs increasing from 121 to 192 °C and 210 to 249 °C, respectively. 35 Lower sublimation vapor pressures have been reported for an increasing number of fluorinated carbons, 52 again providing evidence that shorterchain PFASs are more volatile. Experimental vapor pressures versus temperature for a limited set of PFASs 53 are shown in Figure 1b.…”
Section: Surface Interactions and Volatilitymentioning
confidence: 97%
“…alogVP (mmHg) = 7.97 − 0.16 × F03[C–F] − 3.16 × ACC − 0.64 × n DB.bKwan 71 .cZhang et al . 72 .dBhhatarai and Gramatica 37 .…”
Section: Evaluation Of Existing Qsar/qspr Models For Pfassmentioning
confidence: 99%